Mengungkap Etika Generatif AI: Peran Kreatif Komik Digital dalam Kampanye Kesadaran - Andriani, Yolanda Georgia; Febriani, Shafira; Endarini, Endah Riana; Farhan, Muhammad (Journal of Mandalika Literature, 2025)
The rapid integration of Artificial Intelligence (AI) in Indonesia’s creative industries, including graphic design, animation, music, and digital marketing, has driven efficiency and competitiveness. However, this advancement raises ethical concerns, particularly regarding originality, intellectual property rights (IPR), data privacy, and misinformation. Reports from Kominfo, Populix, and Statista highlight the growing AI adoption and its associated challenges, such as copyright infringement and job displacement. To address these issues, this study proposes the use of digital comics as an effective and relatable medium for ethical AI education, targeting Gen-Z young creatives aged 18–25 who are highly engaged with visual storytelling, digital platforms, and socially conscious content. Using a qualitative approach and Design Thinking methodology, by taking questionnaire samples with indicators of campuses with Visual Communication Design Study Programs in the city of Bandung. The digital comic Maya on the AI Ethic was developed to convey AI ethics through engaging narratives and relatable characters. The results indicate that digital comics enhance awareness of ethical AI usage, fostering a responsible and sustainable creative ecosystem.